Does the chemical signature of TYC 8442-1036-1 originate from a rotating massive star that died in a faint explosion? - Cescutti, Gabriele; Christlieb, Norbert (Astronomy and astrophysics, 2016)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics